Epigenetic Regulator KDM4D Restricts Tumorigenesis via Modulating SYVN1/HMGB1 Ubiquitination Axis in Esophageal Squamous Cell Carcinoma - Yao, Wenjian; Wang, Jianjun; Zhu, Li; Jia, Xiangbo; Xu, Lei; Tian, Xia; Hu, Shuai; Wu, Sen; Wei, Li (Frontiers in Oncology, 2021)
Background: Increasing researches have been reported that epigenetic alterations play critical roles in ESCC development. However, the role of the histone demethylase KDM4D in ESCC tumorigenesis is poorly investigated. This study aims to discover the underlying mechanisms between KDM4D and ESCC progression. Methods: CCK-8 assays, clone formation assay and soft-agar assays were performed to assess cell proliferation. Transwell assay was utilized to assess cell migration efficiency, while sphere formation assay was used to evaluate the cell self-renewal ability. Bioinformatic analysis was conducted to identify prognistic factors and predict the potential E3 ubiquitin ligases. In vitro ubiquitiation assay was conducted to confirm the regulations between SYVN1 and HMGB1. The mRNA levels or protein levels of genes were detected by real-time PCR and western blot analysis. In vivo tumor xnenograft models were used to determine whether the HMGB1 inhibition affected the malignant features of ESCC cells. Result: Epigenome screening and low-throughput validations highlighted that KDM4D is a tumor suppressor in ESCC. KDM4D expressed lowly in tumors that predicts poor prognosis. KDM4D deficiency significantly enhanced tumor growth, migration and stemness. Mechanistically, KDM4D transcriptionally activates SYVN1 expressions via H3K9me3 demethylation at the promoter region, thereby triggering the ubiquitin-dependent degradation of HMGB1. Low KDM4D depended on accumulated HMGB1 to drive ESCC progression and aggressiveness. Targeting HMGB1 (Glycyrrhizin) could remarkably suppress ESCC tumor growth in vitro and in vivo, especially in KDM4D-deficient cells. Conclusions: We systematically identified KDM4D/SYVN1/HMGB1 axis in ESCC progression, proving novel biomarkers and potential therapeutic targets.